Google Earth como ferramenta no processo de ensino dos aspectos físico-naturais do Cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
Education in Brazil is undergoing significant transformations, driven by political and global factors, as well as a rethinking of educational practices. Teachers have reinvented themselves to keep up with changes in the classroom, especially with the use of digital information and communication technologies (DICTs). This research investigated the use of Google Earth as a teaching tool in Geography and, in this sense, analyzed its contributions and limitations to promote understanding and awareness of the physical-natural characteristics of the Cerrado Morphoclimatic Domain, the importance and challenges of its preservation. The work used bibliographic research and didactic sequence (DS) methodologies. Technological advances and challenges in teaching Geography in the educational context of Brazil were addressed, highlighting the importance of geographic reasoning and the need for socially relevant teaching. Geotechnologies in Geography teaching were discussed, exploring the impact of contemporary transformations in the teaching and learning process, as well as pointing out the digital skills necessary for the use of ICTs in the classroom, both for teachers and students, with emphasis on the role of Google Earth. The development of the research was followed by a proposed didactic sequence (DS) for teaching the Cerrado Morphoclimatic Domain using Google Earth. To this end, the characteristics of the Cerrado as a biome and morphoclimatic domain were highlighted, addressing aspects such as climate, relief, vegetation and hydrography. The proposed DS aimed to promote spatial understanding and awareness of the importance of preserving the Cerrado. The results showed that Google Earth, as a didactic tool, can provide greater student engagement in classes, since the mosaic of images offered by Google Earth enabled the three-dimensional and interactive visualization of the Cerrado, making learning more dynamic and stimulating. It is concluded that the tool can facilitate the understanding of geographic concepts and spatial perception of students, since it allows the concrete visualization of the characteristics of climate, relief, hydrography, vegetation and impacts of human action in the Cerrado. The application of the didactic sequence with Google Earth favors the development of students' geographic reasoning, stimulating observation, analysis, interpretation and criticism about the use of geographic space and using the principles and categories of Geography.
Google Earth as a tool in the process of teaching the physical-natural aspects of the Cerrado
Keywords: Google Earth; Ensino de geografia; Domínio morfoclimático do Cerrado; Sequência didática; Google Earth; Geography teaching; Morphoclimatic domain of the Cerrado; Didactic sequence; GEOCIENCIAS::GEOGRAFIA FISICA